Density Functional Theory; A New Route for Structural and Thermodynamic Parameters Calculations - Meikhail, M.S.; Awad, W.; Abdelghany, A.M. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Structural and thermodynamic parameters of the studied virgin polymeric matrices poly e-caprolactone (PCL), Chitosan (Chi) and their polymer blend were investigated using theoretical density functional theory (DFT). Thermodynamic functions were calculated based on vibrational frequencies and optimized geometrical coordinates in the temperature range 25-1000 Â°K which cannot be amended easily. Calculated free energy was found to be convex in terms of extensive variable and concave in terms of intensive ones.